2001
DOI: 10.1507/endocrj.48.63
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Vitamin D Deficiency in Japanese Female Patients with Graves' Disease.

Abstract: Abstract.We reported previously that vitamin D deficiency is a causal mechanism of postoperative tetany in patients with Graves' disease. The aim of the present study was to determine the prevalence of vitamin D deficiency by reviewing serum 25(OH)D levels in 208 patients with Graves' disease (146 women, 62 men) during a 1 year period. Serum 25(OH)D levels were significantly lower (p <0.001) in female Graves' patients (31.8± 13.3 nmol/1) than in male patients (41.3 ± 15.0 nmol/1). Vitamin D deficiency (defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…8,13 Moreover, in the hypothyroid patients, the intestinal motilities were sluggish and it causes the malabsorption of vitamin D and it goes as a vicious cycle. 14 20,21 Hence, usually serum concentration of 25(OH)D is measured as it has longer half-life of 15 days, which was followed in the present study also. Even though increased TSH is used as the marker of hypothyroidism for long time, it is only a feedback mechanism to reduce T3 and T4 and it will elevate during the time the disease has already progressed.…”
Section: Discussionmentioning
confidence: 94%
“…8,13 Moreover, in the hypothyroid patients, the intestinal motilities were sluggish and it causes the malabsorption of vitamin D and it goes as a vicious cycle. 14 20,21 Hence, usually serum concentration of 25(OH)D is measured as it has longer half-life of 15 days, which was followed in the present study also. Even though increased TSH is used as the marker of hypothyroidism for long time, it is only a feedback mechanism to reduce T3 and T4 and it will elevate during the time the disease has already progressed.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, associated myopathy also contributes to fracture by increasing the risk of fall. Low serum vitamin D level has also been established in these patients [3]. Proposed mechanisms are: decreased synthesis in skin due to thyrotoxicosis-associated hyperpigmentation, decreased absorption due to steatorrhea and increased degradation due to hepatic enzyme stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is linear to Vanderpump 2 data which showed peak age of GD incidence to be from 20 to 49 years old. 2 In Japan, Yamashita et al 9 and Yasuda et al 10 study showed mean age of 37 to 39 years old.…”
Section: Vitamin D Il-4 and Ifn-γ Level Before And After Sun Exposurmentioning
confidence: 97%
“…This finding is similar to the results of studies done in Japan. Yamashita et al 9 showed that vitamin D level of male and female GD subjects are 16.54±6.00 and 12.74±5.33 ng/mL. Yasuda et al 10 also showed that vitamin D level of new onset female GD patients of 14.4±4.9 ng/mL.…”
Section: Vitamin D Il-4 and Ifn-γ Level Before And After Sun Exposurmentioning
confidence: 98%